2(3x-6)=3(2x-5)

Simple and best practice solution for 2(3x-6)=3(2x-5) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2(3x-6)=3(2x-5) equation:


Simplifying
2(3x + -6) = 3(2x + -5)

Reorder the terms:
2(-6 + 3x) = 3(2x + -5)
(-6 * 2 + 3x * 2) = 3(2x + -5)
(-12 + 6x) = 3(2x + -5)

Reorder the terms:
-12 + 6x = 3(-5 + 2x)
-12 + 6x = (-5 * 3 + 2x * 3)
-12 + 6x = (-15 + 6x)

Add '-6x' to each side of the equation.
-12 + 6x + -6x = -15 + 6x + -6x

Combine like terms: 6x + -6x = 0
-12 + 0 = -15 + 6x + -6x
-12 = -15 + 6x + -6x

Combine like terms: 6x + -6x = 0
-12 = -15 + 0
-12 = -15

Solving
-12 = -15

Couldn't find a variable to solve for.

This equation is invalid, the left and right sides are not equal, therefore there is no solution.

See similar equations:

| 75+x+x+x=180 | | a+270=-5a-6 | | 100x^3=10000000000 | | 9x-y+4z=-12 | | -5a-3=a+285 | | 2y^2-11y^1+12y=0 | | p-108=-2p-9 | | p-108=-29-9 | | 3x^2*3=0 | | -3e+8=e+80 | | 2r^2-11r+12=0 | | h+128=-2h+5 | | 0.89(x)-8.75=21-0.86(x) | | 9(3y-2)y=2 | | 5(x-3)+8=14(x)+2 | | 0.5a=5(1.25)12.50 | | t-103=-t-7 | | 2y^2-3y^1-4y=0 | | 0.8z=0.3z | | x^2+16k+60=5 | | -c-5=c+93 | | 2.5a=5(1.25)12.50 | | n-65=-n-9 | | 1n+2n= | | x-59=-x-9 | | f(-5)=2x+3 | | y=.10x+2.40 | | -b+8=b+54 | | c+82=-c+4 | | x^2-72x-89=0 | | x^2-882x-98=0 | | 5x+10y=20+5y |

Equations solver categories